2023
DOI: 10.1186/s10195-023-00711-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mortality rate and septic and aseptic revisions in total hip arthroplasties for osteoarthritis and femoral neck fracture: an analysis of the German Arthroplasty Registry

Abstract: Background Indications for total hip arthroplasties (THA) differ from primary osteoarthritis (OA), which allows elective surgery through femoral neck fractures (FNF), which require timely surgical care. The aim of this investigation was to compare mortality and revisions in THA for primary OA and FNF. Methods Data collection for this study was performed using the German Arthroplasty Registry (EPRD) with analysis THA for the treatment of FNF and OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This is similar to the osteoarthritis cohort in the present study (0.12%) [ 12 ], . Large differences in the one-year mortality between patients having undergone arthroplasty for either osteoarthritis or hip fracture were also observed in a recent German Arthroplasty-based study by Szymsky et al [ 17 ], 12.6% compared with 3% respectively.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This is similar to the osteoarthritis cohort in the present study (0.12%) [ 12 ], . Large differences in the one-year mortality between patients having undergone arthroplasty for either osteoarthritis or hip fracture were also observed in a recent German Arthroplasty-based study by Szymsky et al [ 17 ], 12.6% compared with 3% respectively.…”
Section: Discussionmentioning
confidence: 55%
“…There are also several recent studies that have assessed hip arthroplasty for the treatment of hip fractures. The crude mortality has in several of these studies showed a higher early mortality rate associated with cemented hip arthroplasty [ 13 17 ]. Studies have mostly focused on elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Different combinations of wear materials determine the different mechanical characteristics of the arthroplasty 17 19 . The harder the material, the lower the surface roughness and the lesser the vulnerability to deformation forces 20 22 . The diameter of the femoral head plays a crucial role in wear: small femoral heads present less wear consumption because friction is reduced while large femoral heads have greater stability and lower dislocation rate 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In Germany the highest in-hospital mortality rate was recorded at 64.7 per 1,000 patients and intensive care unit (ICU) treatment was documented in 27.7% of cases (8). Intriguingly, in contrast to diagnoses such as major amputations, VO demonstrates comparatively lower mortality rates (10,11). The treatment of elderly patients, who are particularly vulnerable to these infections, is becoming increasingly important due to epidemiological development and the growing prevalence of comorbidities in an aging population (12).…”
mentioning
confidence: 99%